The Bible, literature and communication: A theologian’s view - Jódar, Carlos (2022)
The importance of the Bible from the literary point of view is evident. It has had and continues to have a great influence on literary works, not only as a culturally significant religious text, but also as a literary work of merit in its own right. This article reflects on the extent to which this well-known feature of the Bible might be relevant to the work of a theologian who receives it as a sacred text. First of all, a review is made of the reception of the literary dimension of the Bible throughout history. For various reasons this dimension has tended to be historically underestimated but, at the same time, it was usually admitted that ignoring it was tantamount to compromising the very functionality of the biblical text. There follows a theoretical reflection on the role of literary language in two important areas for theology: the communication of spiritual experience and the representation of history. Finally, a possible classification of biblical contents is proposed according to their literary characteristics and the conditions they establish from the point of view of communication.
Keywords: literary genres; Storytelling; Theology; Poetics; Literature; Bible